Evaluasi Kualitas Website Forum Paud Terhadap Kepuasan Pengguna Menggunakan Metode Web Equal 4.0 - Widodo, Wahyu; Ayun, Qurratu (Journal of Digital Ecosystem for Natural Sustainability, 2022)
Web Forum is a form of mass media published through the internet that can be accessed anywhere and anytime. To determine the quality of a website, it is necessary to measure so that the quality of a website can be known from user perceptions.This study uses the WebQual method which has been modified by adding the dimensions of Website Design and user satisfaction with the three main dimensions of WebQual 4.0, namely Usability, Information Quality, and Service Interaction.The object of this research is the Ngaglik Early Childhood Forum Website. The population of this research is the web admin of PAUD Ngaglik Sleman. The results obtained in this study are that the quality of usability, quality of information and quality of design have a positive effect on user satisfaction. The quality of interaction services has a negative effect on user satisfaction of the Ngaglik PAUD website.